Evaluation of Clinical Single Dental Implants Made between 2013 and 2017 - Erdoğmuş, Zozan (UI Scholars Hub, 2020)
Objective: This retrospective study aimed to determine the profile of patients who underwent single tooth implants between 2013 and 1017 and to evaluate long-term follow-up and success. Methods: The results of 79 patients who underwent single dental intra-bone dental implantation in Diyarbakır Oral and Dental Health Hospital between 2013 and 2017 were evaluated separately in terms of gender, age, implanted area and number, systemic diseases affecting implant health, and missing implants. Results: In this study, single tooth implants were evaluated in 79 patients with a mean age of 39.55 years in men and 30.44 years in women. The 79 dental implants were placed as follows: 6.32% (n = 5) of the lower jaw anterior, 16.45% (n = 13) of the lower jaw premolar, 29.11% (n = 23) of the lower jaw posterior; 11.39% (n = 9) of the upper jaw anterior, 13.92% (n = 11) of the upper jaw premolar, and 22.78% (n = 18) of the upper jaw posterior. Smoking was observed in anamnesis taken from 47 patients. The patients were evaluated in terms of systemic disease risk groups. Conclusion: Dental implantation is the most preferred treatment option in adult patients with single tooth deficiencies with success rates up to 96.34%.